The role of new media in developing political awareness among Omani university youth: Ash Sharqiyah University in the Sultanate of Oman as a model - Almatari, Ali Said Sulaiyam; Alowaicy, Juma Marzouq Amer; Albadowi, Abdullah Saaiyed Abdullah (Journal of Humanities & Social Sciences, 2020)
The study aims to identify the role of the new media in developing political awareness among Omani university Students. The study sample consisted of (91) students from Ash Sharqiyah University in the Sultanate of Oman in the first semester of the academic year 2018- 2019. This study is part of a descriptive research that relies on the survey methodology. Mentioning below the most important results of the study: One of the most sites that students prefer using is Facebook with (76.92%). The presence of moderate cognitive, emotional and behavioral effects achieved by the Omani university students as a result of their reliance on new media sites to follow up on political issues. The Omani university students do not have more than one account on social media sites (62.6%). There is an intermediate level of motivation by the Omani university students for new media sites. There are reasons for Omani university students to rely on new media sites to pursue political issues at an average degree. There are statistically significant differences at the level of (less than 0.05) in the field of incitements of use of new media sites due to the gender variable in favor of females. There are no statistically significant differences at a level (less than 0.05) in the motives using new media in general or for political reasons and the reasons why Omani university student relying on new media sites according to the variable of the school year and the college type. The study recommends that university students should be careful in publishing in new media sites and educational sessions and seminars should be held by the competent authorities to educate young people about how to use the security of new media sites.